Effect of Chemically Treated Buffing Dust on Technological Properties of Tyre Tread Compounds - Wellappili, Champa J.; de Silva, Karnika; Dharmatilake, Malani; Denawaka, Indra (Progress in rubber, plastics and recycling technology, 2007)
Polymer blends have become a very important subject for scientific investigation because of their growing commercial acceptance. This research aimed to investigate the possibilities of blending chemically treated buffing dust, a cheap reinforcing filler in virgin natural rubber (NR) systems to obtain improved properties. A series of experiments were carried out with three types of blend - namely NR with untreated buffing dust, fatty acid (FA) treated buffing dust and De-link treated buffing dust. Pre-conditioning of buffing dust by treating with De-link showed improvements in all properties when compared to blends with untreated buffing dust. Further improvement of physical properties was achieved through a blending process where buffing dust was first treated with a FA, before the actual blending with NR compound was carried out. FA based activator seems to improve the miscibility of the two phase through possible plasticizing action thereby improving the physical properties of the end product. It is clear that the incorporation of the FA could be a cheaper alternative to achieve better dispersibility of buffing dust in NR phase to improve the properties of blends.